2013
DOI: 10.1080/02699931.2012.716394
|View full text |Cite
|
Sign up to set email alerts
|

Children's responses to cognitive challenge and links to self-reported rumination

Abstract: We tested the hypothesis that less effective responses during a cognitive challenge would relate to higher levels of self-reported rumination in children. The sample was 100 children (55 boys, 45 girls), aged 7 – 14 years. A portion (n = 65) was at high risk for depression due to having a parent with a childhood-onset mood disorder, and 35 were a low-risk comparison group. Using an impossible puzzle task, we assessed children’s responses following failure across several domains: emotions (expressed anger, sadn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Clustering at the family level for these two-parent families accounted for a significant amount of the variance in four of the dependent variables, including parents’ respect others and country (Intraclass Correlation Coefficient (ICC) = .25, p < .001) and community service (ICC = .43, p < .001) messages and adolescents’ respect others and country (ICC = .73, p < .001) and standard political involvement (ICC = .86, p < .001) messages. To both account for this non-independence, and following similar procedures as researchers using random-effects models with family data (e.g., Gentzler, Wheat, Palmer, & Burwell, 2013), a multilevel approach was used with parents nested within families.…”
Section: Methodsmentioning
confidence: 99%
“…Clustering at the family level for these two-parent families accounted for a significant amount of the variance in four of the dependent variables, including parents’ respect others and country (Intraclass Correlation Coefficient (ICC) = .25, p < .001) and community service (ICC = .43, p < .001) messages and adolescents’ respect others and country (ICC = .73, p < .001) and standard political involvement (ICC = .86, p < .001) messages. To both account for this non-independence, and following similar procedures as researchers using random-effects models with family data (e.g., Gentzler, Wheat, Palmer, & Burwell, 2013), a multilevel approach was used with parents nested within families.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies also have suggested that resting CVC may be negatively associated with specific aspects of depression rather than the syndrome as a whole, such as somatic, anhedonic, and melancholic symptoms (Bosch et al., ; Chen et al., ; Kemp et al., ) and insomnia (Rottenberg et al., ). Findings from recent studies of CVC reactivity have provided evidence that is similarly mixed, including studies documenting the hypothesized negative association between CVC reactivity and symptoms of depression (Choi et al., ; Gentzler et al., ; Oppenheimer et al., ; Rottenberg, ; Shinba et al., ), yet others failing to find the expected association (El‐Sheikh et al., ; Fagundes et al., ; Gentzler et al., ; Shenk et al., ; Yaroslavsky et al., ). Other studies only showed an association with cognitive aspects of depressive symptoms (Gordon et al., ), or when examining interactions between CVC at rest and CVC reactivity (Yaroslavsky et al., ).…”
Section: Theory and Evidence For Components Of Flexibilitymentioning
confidence: 99%
“…Working memory is assessed at the 3½‐year‐old visit with the WPPSI‐IV picture memory test 44 . Emotion Regulation is assessed by the Toy‐behind Barrier, the Disappointing Gift, and the Impossible Puzzle Box Tasks at 3½, 5, and 7 years, respectively, 45‐48 and 7‐year‐old children self‐rate their emotions during this task by pointing to predrawn pictures displaying a range of emotions. Planning ability is evaluated by the Tower of Hanoi task of age‐appropriate difficulty 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Assay results for these substances were reported only as positive or negative, with a cut-off of 2.5 ng/mL for positivity. We TA B L E 1 Caregiver protocol and schedule of events Cognition fluid composite; cognition early childhood composite (NIH Toolbox) 34 Emotion regulation a Toy-behind barrier 45 Disappointing gift 46 Impossible puzzle box 47,48 Self-reported emotion regulation a n/a n/a Self-rated emotions (pictures)…”
Section: Definition Of Exposure To Marijuana and Other Substances Omentioning
confidence: 99%